Esquemas de políticas de reforma agraria en Colombia - Mariano Arango Restrepo (Lecturas de Economía, 1987)
This paper makes a recount from 1874 as far as today, of the politics which the Colombian state has intended to modify the agrarian structure in this country. Last century colonization laws, the 1936's 200 Law, the 1961's 135 Law and, in short, the more recent projects are presented, both the content and the results.